Influence of Haptic Feedback on a Pointing Task in a Haptically Enhanced 3D Virtual Environment - Corbett, Brendan; Yamaguchi, Takehiko; Liu, Shijing; Huang, Lixiao; Bahn, Sangwoo; Nam, Chang S. (Human-Computer Interaction. Interaction Modalities and Techniques, 2013)
To gain a better view of the value of haptic feedback, human performance and preference in a pointing style task in a three-dimensional virtual environment was explored. Vibration and haptic attractive force were selected as two simple cases of feedback, each with two levels. These types of feedback were compared to a no-feedback condition to better understand how human performance changes under these conditions. The study included 8 undergraduate students. A Novint Falcon haptic controller was used in a simulated three-dimensional virtual environment. Analysis was conducted on how each type of feedback effects the movement time (MT) of users. The results showed that vibration was perceived negatively and had a slight negative impact on performance. The haptic attractive force significantly improved performance and was strongly preferred by subjects.